Language Attitude and Language Choice among Students in Yogyakarta - Anna, Fitriati; Maria, Magdalena Sinta Wardani (Pusat Pengajian Ilmu Kemanusiaan, 2019)
Living in Yogyakarta, a multicultural city in Indonesia, enables people to meet and communicate with those whose different language and cultural backgrounds. Moreover, the existence of Yogyakarta as an international tourist destination, provides more opportunity for the society to mingle with others from different countries. This situation influences the use of the language. It is necessary to choose the most appropriate language to use. In general, people use Javanese language (one of the local languages in Indonesia) to communicate with those who are Javanese and Indonesian to communicate with those from different regions in Indonesia and English when they communicate with foreigners. Nowadays, there is a tendency that the use of Indonesian and English is getting more intense, while the use of Javanese or other local language is fading.